2000
DOI: 10.1038/sj.mp.4000749
|View full text |Cite
|
Sign up to set email alerts
|

Brain Derived Neurotrophic Factor (BDNF) gene variants association with age at onset and therapeutic response in schizophrenia

Abstract: Schizophrenia is a heterogeneous disease involving genetic and environmental factors. The frequency of structural brain abnormalities or physical anomalies supports a neurodevelopmental etiology, especially in early onset schizophrenia. Brain-Derived-Neurotrophic-Factor (BDNF) is involved in the neurodevelopment of dopaminergic (DA)-related systems and interacts with the meso-limbic DA systems, involved in the therapeutic response to antipsychotic drugs and substance abuse. In addition, BDNF promotes and maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
1
4

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(108 citation statements)
references
References 27 publications
9
94
1
4
Order By: Relevance
“…Although population studies have yielded divergent data about the association of variants in the BDNF gene with increased risk and developmental features of schizophrenia, [72][73][74][75][76][77][78] human postmortem studies suggest that individuals with schizophrenia have reduced expression of TrkB and BDNF in the cerebral cortex, 12,[79][80][81][82] as well as decreased BDNF protein levels in the serum. 83 In addition, various animal models of schizophrenia consistently show a downregulation of BDNF transcript or protein.…”
Section: Discussionmentioning
confidence: 99%
“…Although population studies have yielded divergent data about the association of variants in the BDNF gene with increased risk and developmental features of schizophrenia, [72][73][74][75][76][77][78] human postmortem studies suggest that individuals with schizophrenia have reduced expression of TrkB and BDNF in the cerebral cortex, 12,[79][80][81][82] as well as decreased BDNF protein levels in the serum. 83 In addition, various animal models of schizophrenia consistently show a downregulation of BDNF transcript or protein.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF variants have been related to schizophrenia, but only marginal association or negative significance has been described in relation to treatment response. [141][142][143] NOTCH4, a developmental gene also involved in the regulation of neuron generation from stem cells, was not found individually associated with response but was suggested to interact with COMT to influence clinical outcome, 145 although the validity and biological significance of this finding requires investigation. The tumour necrosis factor-a (TNF-a) is a cytokine that mediates host response during inflammation and infection, and has been suggested to play a role in neurodevelopment and degeneration.…”
Section: Developmental and Regulatory Genesmentioning
confidence: 99%
“…BDNF interacts with TrkB receptor tyrosine kinase, playing several important roles such as; promotion of survival, differentiation and maintenance of neurons in peripheral nervous system and central nervous system; influences to axonal growth and connectivity; participation in the local responses to various types of neuronal stress or insults (Manji et al, 2003;Mattson et al, 2003). Furthermore, it also has been reported that the gene encoding BDNF might be an important candidate for susceptibility of neuropsychiatric disorders including bipolar disorder (Neves-Pereira et al, 2002;Sklar et al, 2002;Hashimoto et al, 2004), schizophrenia (Krebs et al, 2000), Parkinson's disease (Momose et al, 2002), and Alzheimer's disease (Ventriglia et al, 2002). In the studies reporting possible association of BDNF and these disorders, two SNPs of BDNF gene has been reported.…”
Section: Introductionmentioning
confidence: 99%